Towards a Hydrogen Economy in the UNECE Region - United Nations Economic Commission for Europe (United Nations, 2024)
The publication proposes a method for hydrogen classification needed to jumpstart production and international trade in hydrogen. It also presents several project ideas in selected UNECE member States that would accelerate deployment of hydrogen.